1998
DOI: 10.1021/ja974112a
|View full text |Cite
|
Sign up to set email alerts
|

Strong Dimerization of Ureidopyrimidones via Quadruple Hydrogen Bonding

Abstract: 6-Methyl-2-butylureidopyrimidone dimerizes via four hydrogen bonds in the solid state as well as in CHCl3 solution via a donor−donor−acceptor−acceptor (DDAA) array of hydrogen bonding sites in the 4[1H]-pyrimidinone tautomer. An intramolecular hydrogen bond from the pyrimidine NH group to the urea oxygen atom preorganizes the molecules for dimerization. The dimerization constant of the dimer in CHCl3 exceeds 106 M-1. In CHCl3 containing DMSO, the dimer is in equilibrium with the monomeric 6[1H]-pyrimidinone ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
664
3
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 765 publications
(704 citation statements)
references
References 24 publications
32
664
3
5
Order By: Relevance
“…These molecules have also received much attention as fundamental synthetic building blocks because of their hydrogen bonding and π-π stacking potential. In particular, Meijer's ureidopyrimidone (UPy) building block [9,10], with its characteristics of a high dimerization constant and synthetic accessibility, has found widespread applications in supramolecular chemistry, materials science, and catalysis [11,12]. Zimmerman's ureidodeazapterin and ureidonaphthyridine modules are also successful examples of heterocyclic building blocks [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have also received much attention as fundamental synthetic building blocks because of their hydrogen bonding and π-π stacking potential. In particular, Meijer's ureidopyrimidone (UPy) building block [9,10], with its characteristics of a high dimerization constant and synthetic accessibility, has found widespread applications in supramolecular chemistry, materials science, and catalysis [11,12]. Zimmerman's ureidodeazapterin and ureidonaphthyridine modules are also successful examples of heterocyclic building blocks [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Polymers with double hydrogen bonds based on amides could be achieved by radical copolymerizations [28][29][30][31] or polycondensation. [32] These copolymers have a good water solubility due to the amide groups and the strength of intermolecular hydrogen bonds which have been qualitatively [28] or quantitatively [32] studied by NMR at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Sessler et al 12,13 developed a non-covalently assembled supramolecular system based on Watson-Crick-type nucleic acid base pairing interactions, and the hydrogen bonds provided an effective pathway for mediating the electron transfer process. The 2-ureido-4[1H]-pyrimidinone motif reported by Meijer et al 14 represents a fascinating self-complementary quadruple hydrogen bonding module and Tung et al 15 have shown that the triplet energy transfer can occur via a 'through bond' mechanism in this system. Our research group also provided an example that the hydrogen bonding and salt-bridges can mediate the triplet energy transfer.…”
Section: Introductionmentioning
confidence: 99%